(3bUjOI aj eOM GdfHj Udi Gddg Ydjg hSdes - (3CMeO GdWjH Hf eMeO GdUGdM Hf SdjeGf GdYjShj,J (B1251 (3g` s
(3ChdgG (B:s
(3caaJ SLGd GdOeY aCfgd hGfJKQ hYGO YbjbkG HYOeG cGf cGdOQQ s
(3BNQgG (B:s
(3hSde SdGekG dG GfJgGA dMOg jchf aj GdOfjG haj GdBNQi dfG GdaNQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B141 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B256s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3O (B1475) s
Keywords: (3GdCOHs